Correlação entre o diagnóstico ultrassonográfico pelo sistema BI-RADS e os resultados cito e histopatológicos das lesões mamárias - Façanha, Luiz Henrique Ferreira (2009)
Aims: evaluating ultrasound features of breast lesions, by applying them ultrasound BI-RADS (US-BI-RADS) classification, as well as correlating them to their respective cytopathologic and histopathologic diagnoses, collected by fine-needle aspiration biopsy (FNAB), core biopsy, and excision biopsy. Investigating the agreement between US-BI-RADS and cytopathologic FNAB classification to determine benign or malign lesions. Evaluating sensibility, specificity and accuracy of core biopsy, oriented by ultrasonography, in BI-RADS diagnosis for benign and malign lesions determination. Comparing histopathologic core biopsy and excision biopsy results, evaluating the agreement between both methods. Methods: sequential study of 205 patients with breast lesions diagnosed by US-BI-RADS system, from Maternidade-Escola Assis Chateaubriand’s ambulatory, from January of 2007 to July of 2009. After classifying lesions within BI-RADS system, biopsies conducted by ultrasound (FNAB, core biopsy) and excision biopsy were accomplished, and they had their cytopathologic and histopathologic diagnoses evaluated. Statistic analysis was carried out using SPSS 16.0 statistic software for Windows. Data were disposed in tables. Continuous variables were expressed by mean and standard deviation, and categorical variables were expressed by frequency and percentile. BI-RADS classification was evaluated by means of sensibility, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy measurements, taking as a pattern the histopathologic diagnosis that core biopsy and excision biopsy obtained. For evaluating agreement of US-BI-RADS and histopathologic results, this study used the kappa index of concordance, with the significance level of 5%. Results: when FNAB was oriented by ultrasound, this research did not find malignity in category 2, only 1% of malignity in category 3, and 2.5%, 23.1% and 80% (4-A, 4-B, 4-C respectively) in category 4. Category 5 showed 100% of malignity. Insufficient or inadequate results were 17.5%. When the study performed the core biopsy, it did not find malign result in category 2, 2.6% in category 3, and in category 4 it found 10%, 46% and 80% (4-A, 4-B, 4-C respectively). Sensibility was 95.2%, NPV 97.4, and specificity 46.9%. PPV was 31.7% and accuracy 56.9%. The agreement between core biopsy histopathologic result and excision biopsy was 100%. Conclusion: FNAB oriented by ultrasonography showed to be a method with good diagnosis agreement, in benign and malign breast lesions, according to US-BI-RADS, although the occurrence of insufficient or inadequate biopsies was high (17.5%). Core biopsy showed to be a high sensitivity method; nonetheless it shows a low specificity in determining benign and malign lesions, according to US-BI-RADS. When compared with excision biopsy results, core biopsy histopathologic results showed 100% of agreement.